2000
DOI: 10.1590/s0034-71672000000200011
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da satisfação de um grupo de idosas e cuidadores com o planejamento de alta

Abstract: Independently of the type of quality assistance improvement model chosen in a health institution, the implementation of ways of assessing it is also necessary. This study analyze the degree of satisfaction among a group of 50 hospitalized elderly women and/or caretakers after the implementation of a discharge planning in a Emergency Medical Clinic Unit. The present paper also investigates the need for continued assistance and points out which information is considered the most important by the patient. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
6

Year Published

2005
2005
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 6 publications
1
4
0
6
Order By: Relevance
“…Of the thirteen studies that demonstrated DP satisfaction, six (12)(13)(14)(15)(16)(17) employed descriptive approaches, three with longitudinal orientation (18,20,24) , one (19) nearlyexperimental, one (21) experimental, and two (22)(23) metanalyses. However, the authors of the two metanalyses (22)(23) argue that the studies analyzed showed results with little significant evidences, because of the applied orientation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the thirteen studies that demonstrated DP satisfaction, six (12)(13)(14)(15)(16)(17) employed descriptive approaches, three with longitudinal orientation (18,20,24) , one (19) nearlyexperimental, one (21) experimental, and two (22)(23) metanalyses. However, the authors of the two metanalyses (22)(23) argue that the studies analyzed showed results with little significant evidences, because of the applied orientation.…”
Section: Discussionmentioning
confidence: 99%
“…Five studies (17)(18)(19)(20)(21) showed DP satisfaction stemmed to the educational strategy application which considered the patient health status, that is, information with specific content about the disease and treatment resume, use of audiovisual resources suitable to their educational characteristics. There was an atmosphere that allowed active participation and their expectations were met.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Idoso e o Cuidado de Enfermagem Idoso e o Cuidado de Enfermagem Idoso e o Cuidado de Enfermagem Idoso e o Cuidado de Enfermagem Idoso e o Cuidado de Enfermagem A assistência de Enfermagem ao idoso é dispensada tanto no ambiente institucional, como no domiciliar e objetiva atender às necessidades básicas afetadas desse grupo, para conceder-lhe melhor qualidade de vida (9) . A enfermagem busca criar um ambiente que proporcione ao idoso condições adequadas para sua recuperação, bem como a ênfase na educação em saúde, procurando promover a redução da morbi-mortalidade.…”
Section: Cuidado Ao Idoso Institucionalizado Cuidado Ao Idoso Instituunclassified
“…O referencial teórico mais utilizado por estudiosos no processo de avaliação em saúde foi estabelecido por Donabedian que aborda estratégias avaliativas nas áreas de estrutura, possibilitando a avaliação do ambiente onde se desenvolve o processo de cuidados, processo que disponibiliza avaliação do ponto de vista técnico e científico, e resultado que evidência o sucesso e qualidade da assistência oferecida ao paciente, e assim, atingir os objetivos propostos, que seriam os de promoção, proteção e recuperação da saúde (4) . Sabe-se que a preocupação com a avaliação dos serviços de saúde vem se manifestando entre outros fatores em conseqüência do aumento da população brasileira na faixa etária dos 65 anos ou mais (5) . Porém, com o aumento dos custos com a atenção à saúde, e principalmente com aumento de doenças crônico-degenerativas que acompanham o crescimento da população, torna-se importante que a avaliação em saúde esteja baseada nas necessidades da população, permitindo a melhora da qualidade de vida.…”
Section: Introductionunclassified